Urban Networks in the Roman Province of Achaia (Peloponnese, Central Greece, Epirus and Thessaly) - Karambinis, Michalis (Journal of Greek Archaeology, 2018)
It is generally accepted that the late-Hellenistic era (c. 150–31 BC) was a period of disturbance for Greece. The wars between Republican Rome and the Hellenistic kingdoms as well as the Roman civil wars took place in major part on Greek soil. The ancient writers of late-Hellenistic but also of Imperial times (e.g. Polybios, Strabo, Plutarch, Dio Chrysostom and Pausanias) speak of ruins, depopulation and decline, and in fact this turbulent situation had negative effects both at province and city level. ‘Augustus and his successors tried to stop this decline by introducing some changes which favoured some large cities,’ but how successful were these changes in recovering the cities of Greece at a general level is not clearly defined.